Identifying biased test items by differentia Item Functioning Analysis Using contingency table approaches a comparative study - Pedrajita, Jose Q. (Education quarterly.)
This study identified biased test items through differential item functioning analysis using four contingency table approaches: Chi-Square, Distracter Response Analysis, Logistic Regression, and Mantel-Haenszel Statistic. The study made use of test scores of 200 junior high school students. One hundred students came from a public school, and the other 100 were private school examinees. One hundred students were males and 100 were females. Basing from their English II grades, 95 students were classified as low ability and 105 as high ability students. A researcher-constructed and validated Chemistry Achievement Test was used as research instrument. The results from the four methods used were compared, and it was found that school type, gender, and English ability bias exists. There was a high degree of agreement between the Logistic Regression and the Mantel-Haenszel Statistic in identifying biased test items.